Participation to avoid elite capture in communication policies: Lessons from Latin America - Linares, Alejandro Felix; Segura, Maria Soledad (Observatorio (OBS*), 2023)
How did face the participatory state institutions of communication policies created in Argentina, Ecuador, Mexico and Uruguay the capture by political and economic elites? This article answers this question through a comparative approach. The research addresses regulation and its implementation based on the methodological guide provided by the concept of citizen participation. Diversity, implementation, incidence, autonomy and transparency are the axes that organized the analysis that includes qualitative and quantitative information built from documents, specific bibliography and interviews. It concludes that participatory bodies occasionally limited the capture of policies or generated valuable experiences in that search, at least temporarily. However, these entities failed to prevent the capture of the policies by economic and political elites. Therefore, they did not reach enough influence to change the communication system. Despite this, it may list a set of unintended and difficult-to-measure positive results that show the enrichment of democratic and civic practices.